BRAF mutation in hairy cell leukemia - Ahmad Ahmadzadeh; Saeid Shahrabi; Kaveh Jaseb; Fatemeh Norozi; Mohammad Shahjahani; Tina Vosoughi; Saeideh Hajizamani; Najmaldin Saki (Oncology Reviews, 2014)
BRAF is a serine/threonine kinase with a regulatory role in the mitogen-activated protein kinase (MAPK) signaling pathway. A mutation in the RAF gene, especially in BRAF protein, leads to an increased stimulation of this cascade, causing uncontrolled cell division and development of malignancy. Several mutations have been observed in the gene coding for this protein in a variety of human malignancies, including hairy cell leukemia (HCL). BRAF V600E is the most common mutation reported in exon15 of BRAF, which is observed in almost all cases of classic HCL, but it is negative in other B-cell malignancies, including the HCL variant. Therefore it can be used as a marker to differentiate between these B-cell disorders. We also discuss the interaction between miRNAs and signaling pathways, including MAPK, in HCL. When this mutation is present, the use of BRAF protein inhibitors may represent an effective treatment. In this review we have evaluated the role of the mutation of the BRAF gene in the pathogenesis and progression of HCL.